Tunneling-nanotube direction determination in neurons and astrocytes - Sun, X (Nature Publishing Group, 2012)
A tunneling nanotube (TNT) is a newly discovered structure involved in cell–cell communication and is found in various types of cells. Here we identify S100A4 as an extracellular molecule and describe its role in attracting the growth direction of TNTs. Together with its putative receptor, receptor for advanced glycation end product, we demonstrate their involvement in TNT direction guidance. Our results further suggest a mechanism for direction guidance of TNTs. In TNT-initiating cells, p53 activates caspase-3, which leads to S100A4 cleavage and its subsequent decrease in cellular concentration. The decrease in cellular S100A4 induces the formation of a gradient of S100A4, from a low concentration in initiating cells toward a high concentration in target cells. This concentration gradient of S100A4 induces direction guidance for TNTs.